Backlight Imaging Based on Laser-Gated Technology - Jinzhou Bai; Hengkang Zhang; Huiqin Gao; Shaogang Guo; Siyuan Wang; An Pan (Photonics, 2024)
Backlight imaging refers to the process of capturing images when the light source directly enters the lens of imaging devices or against a high-brightness background, which usually suffers from degraded imaging quality caused by direct or reflected strong light. Traditional backlight imaging methods involve reducing light flux, expanding dynamic range, and utilizing avoidance angles. However, these methods only partially address the issue of backlighting, and are unable to effectively extract information from the areas overwhelmed by the backlight. To overcome these limitations, this paper reported a backlight imaging technique based on active illumination laser gated imaging technology (AILGIT), originally applied in underwater scattering imaging. Given that backlight imaging is essentially a form of scattering imaging, this technique is likely applicable to backlight scenarios. The AILGIT employs nanosecond-gated imaging components synchronized with nanosecond pulse laser illumination to spatially slice the target. This method allows the camera to capture target signals within specific slices only, which effectively suppresses ambient light and scattering interference from the medium and achieves high-contrast imaging with strong backlight suppression. Experiments obtained dynamic backlight imaging results for a vehicle with headlight on at night from a distance of 500 m, with 60 frames per second and a 4.2 by 2.8 meters’ field of view, where wheel contours and the license plate can be clearly distinguished. The result not only demonstrates the potential of AILGIT in suppressing strong backlight, but also lays the foundation for further research on laser 3D imaging and subsequent processing techniques for backlight targets.